2019
DOI: 10.31703/grr.2019(iv-i).09
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Strategies for the Effective Implementation of Early Childhood Education Programme in Punjab

Abstract: The present study aimed to propose strategies for the effective implementation of Early Childhood Education Programme in government schools in Punjab. A sample of 300 heads of educational institutions was taken from the 36 districts of Punjab to evaluate this programme. A questionnaire was used to collect the opinion of the heads of educational institutions. The findings of the study show that physical facilities were provided by the government for the implementation of ECE programme in only 1000 schools in Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Shore, 1997;Mustard & McCain, 1999) which concluded that rich and dynamic learning environment is thought to be helpful in enhancing brain development, social development and physical development. Likewise, a number of other studies (i.e., Ahmad et al, 2019;WHO, 2004& Murtaza, 2011 also support findings of this research study. Findings of their research showed that ECE can play important role in the development of a child.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Shore, 1997;Mustard & McCain, 1999) which concluded that rich and dynamic learning environment is thought to be helpful in enhancing brain development, social development and physical development. Likewise, a number of other studies (i.e., Ahmad et al, 2019;WHO, 2004& Murtaza, 2011 also support findings of this research study. Findings of their research showed that ECE can play important role in the development of a child.…”
Section: Discussionsupporting
confidence: 89%
“…Many countries of world adopt play based learning for Kachi class and give it name of ECE. ECE has very important role in the development of young generation of any nation (Ahmad et al, 2019). The school learning in the form of ECE and home environment for learning can be helpful to make a student successful not only during his studies but in his future life as well (Murtaza, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The reviewed empirical studies have identified the importance of human resources as support for maintenance of standards and quality for actual implementation of ECE. The studies also revealed that availability of human resources for ECE affect positively the implementation of early childhood education and therefore improve their academic attainments (Ahmad et al, 2019;Chikwiri & Musiyiwa;Bureta, 2021;Shemahonge, 2018;Mbagala & Shukia, 2019). However, despite the fact that provision of early childhood education in Tanzania is compulsory and fee-free in public primary schools for all children under 6 years, little attention has been made on the adequacy of human resources on the implementation of early childhood education.…”
Section: Empirical Reviewmentioning
confidence: 98%
“…Different scholars have conducted several studies related to this aspect inside and outside of Tanzania. In India, Ahmad et al (2019) conducted a study to propose strategies for the effective implementation of Early Childhood Education Programme in government schools in Punjab, India. The study employed mixed approach.…”
Section: Empirical Reviewmentioning
confidence: 99%